ADDRESSING DESERTIFICATION TO PROMOTE SUSTAINABLE PEACE BETWEEN FARMERS AND HERDSMEN IN NIGERIA - Sani Sani Ibrahim (International Studies Journal)
Desertification is the reflection of the environmental problem facing Nigeria today, it is estimated that the country is losing about 350,000 hectares to desertification annually, affecting almost the northern part of the country.Series of government efforts were made to address the issue but due to the gap between policy and implementation, the situation keep advancing to southwards at the rate of 1.5 km per year.Thus, desertification is a growing ecological problem, causing economic losses, threatening national unity, as well undermining the country’s national security. The purpose of this research are  to: (1) examine the role of climatic variability and human factors to  desertification and its (desertification) impact to national security; (2) suggest appropriate measures to address desertification for sustainable peace between farmers and herdsmen.  The research is situated within the theoretical framework of Political Economy Approach, to explain economic issues as the primary cause of tension and conflict between Farmers and Herdsmen in their struggle for economic survival. The method in obtaining data for this research was mainly through secondary.Two major findings emerged from the research; (1) Desertification a source of conflict and threat to national security and (2) Strategic intervention to curb desertification for sustainable peace. The research recommends the adoption all the strategic intervention measures to counter climate change and excessive human activities toward the successful recovery of the land productivity for sustainable peace.